EFEKTIFITAS APLIKASI KRAPYAK-U SEBAGAI ADMINISTRASI KEPESANTRENAN DIGITAL DI PONDOK PESANTREN ALI MAKSUM KRAPYAK YOGYAKARTA - Ahmad, Amala Bilqis (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
Digital boarding school administration is a digital boarding school management concept that involves the use of information and communication technology (ICT) in various aspects of boarding school activities. In digital pesantren administration, all administrative activities are carried out through digital platforms such as websites, mobile applications, or information management systems (SIM) to optimize the efficiency and productivity of pesantren management. This abstract will discuss several main aspects of digital boarding school administration, including the benefits and challenges of implementing them. One of the main benefits of digital boarding school administration is increased efficiency and accuracy in administrative management, such as making financial reports, managing student data, and processing payments. This can also facilitate communication between administrators, teachers, and students. Krapyak-U as a form of implementing digital boarding school administration is expected to become a platform for facing certain challenges, such as data security and information integrity, lack of technology accessibility for certain users, and decreased interpersonal interaction between administrators and students. Therefore, Islamic boarding school managers need to carefully consider the benefits and challenges of implementing digital Islamic boarding school administration, and choose a platform that suits the needs and capabilities of the Islamic boarding school. Several information technology applications that can be used for digital boarding school administration include educational information management systems (SMIP), e-learning platforms, academic information systems, financial and accounting applications, and dormitory management applications. Through the use of this information technology, Islamic boarding schools can facilitate various administrative processes, such as registration of new students, payment of tuition fees, financial management, class management, monitoring the progress of students, etc. As for Krapyak-U, it was raised at the time of COVID-19, this made digital boarding school administration even more relevant and important. With social restrictions and restrictions on movement, information technology can be an alternative to maintain connectivity between administrators, students and other stakeholders. In addition, the use of information technology can also help all elements of the Islamic boarding school to continue learning and interacting even though they are not in the physical environment of the pesantren. Thus, digital pesantren administration can provide many benefits and opportunities for Islamic boarding schools in facing challenges and opportunities in the digital era.